Overground robotic exoskeleton vs conventional therapy in inpatient stroke rehabilitation: results from a pragmatic, multicentre implementation programme - Pui Kit Tam; Ning Tang; Nur Shafawati Binte Kamsani; Thian Yong Yap; Ita Coffey-Aladdin; Shi Min Goh; Jean Pei Pei Tan; Yook Cing Lui; Rui Ling Lee; Ramaswamy Suresh; Effie Chew (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Despite the reported efficacy of overground robotic exoskeleton (ORE) for rehabilitation of mobility post-stroke, its effectiveness in real-world practice is still debated. We analysed prospectively collected data from Improving Mobility Via Exoskeleton (IMOVE), a multicentre clinical implementation programme of ORE enrolling participants with various neurological conditions and were given options to choose between 12 sessions of ORE or conventional therapy (control). Methods This is analysis of participants under IMOVE who fulfilled the following criteria (i) primary diagnosis was stroke (ischemic, hemorrhagic; first or recurrent), (ii) onset of stroke was within 9 months and (iii) the intervention was during inpatient stay. They should also fulfill the general IMOVE inclusion and exclusion criteria which were resembling general clinical and manufacturing criteria of ORE. Outcome measures included Functional Ambulatory Category (FAC), Rivermead Mobility Index (RMI), Functional Independence Measure (FIM) and Clinical Outcome Variable Scale (COVS), measured immediately before and after the 12 sessions of therapy, and mean distance walked per session. Results Of 149 participants (105 OREs and 44 controls), both groups improved significantly in motor outcomes with no significant between-group differences. Participants with baseline FAC 1 had significantly greater improvement in motor sub-score of FIM (FIM-motor) compared to controls (mean difference 8.4, 95% CI 0.65–16.07, ηp 2 = 0.136, p = 0.034). The mean distance walked per session for ORE group was almost three times that of control for those with baseline FAC 0 (121.5 [SD 31.1]m vs 35.0 [SD 41.0]m, 95% CI 62.2–110.9, d = 2.54 p < 0.001) and FAC 1 (145.8 [SD 31.6]m vs 52.2 [SD 42.5]m, 95% CI 61.8–125.2, d = 2.71, p < 0.001). The difference was not observed for FAC 2 to 3 (162.9 [SD 29.2]m vs 134.2 [SD 87.5]m, 95% CI −22.2 to 79.7, d = 0.41, p = 0.252). Conclusion In a pragmatic setting, use of ORE for gait training enabled patients with lower ambulatory capacity to walk longer distances during therapy sessions. Patients who required continuous assistance during ambulation (FAC 1) had significantly better gains in FIM-motor compared to conventional therapy, suggesting possible benefit of ORE for this group. Trial Registration The trial was registered with clinicaltrials.gov (NCT05659121) on April 14, 2022.